The effects of parental divorce on self- esteem, anger, substance use and family aspects among young people - Hanna Margrét Heimisdóttir 1997- (2021)
The prevalence of divorce has increased in recent decades, but it can negatively affect children’s well-being and behavior. The aim of this cross-sectional study was to examine the effects of parental divorce on self-esteem, anger, daily cigarette smoking, lifetime drunkenness, drug use, parental support, and parental monitoring among young people. The data came from The Youth in Iceland 2016 survey which was conducted by Icelandic Centre for Social Research and Analysis. There were 10.717 valid responses from high school students collected in the Youth in Iceland 2016 survey, with a response rate of 71%. A simple random sample was used for this study, consisting of 2.165 participants, 1.058 (48.9%) males and 1.071 (49.5%) females, ranging from 15 to 21 years of age. The results showed that participants from divorced families reported lower self-esteem, received less parental support, less parental monitoring, and reported more anger, daily cigarette smoking, lifetime drunkenness and drug use than participants from non-divorced families. Linear regression showed that parental monitoring mediated the effects of parental divorce on daily cigarette smoking, lifetime drunkenness and drug use. In addition, parental support mediated the effects of parental divorce on self-esteem and anger. This study showed the importance of parental support and monitoring on self-esteem, anger, daily cigarette use, lifetime drunkenness, and drug use among young people who had experienced parental divorce. Keywords: Parental divorce, self-esteem, anger, daily cigarette smoking, lifetime drunkenness, drug use, parental support, parental monitoring, young people Algengi skilnaðar hefur aukist undanfarna áratugi, en skilnaður getur haft neikvæð áhrif á andlega heilsu og hegðun barna. Markmið þessarar þversniðsrannsóknar var að skoða áhrif skilnaðar foreldra á sjálfsvirðingu, reiði, daglegar reykingar, ölvunar, vímuefnanotkunar, stuðnings foreldra og eftirlit foreldra meðal ungs fólks. Gögnin sem notuð voru í þessari rannsókn voru frá ...